Intepretasi Tindak Tutur Penggunaan Ragam Bahasa Model Martin Joos pada Berita Online - Nuryansyah Adijaya; M. Yanuardi Zain; Febriyantina Istiara; Dayana, Yuliana Fatima (LPPM STKIP PGRI Bandar Lampung, 2024)
Interpretation in communication plays an important role in understanding the message conveyed in every utterance. However, disagreements sometimes arise because the receiver of the message interprets the utterance differently. This study aims to delve deeper into the interpretation of speech acts in the use of language varieties, particularly the use of frozen language variety in online media reporting. A qualitative descriptive method is used in this research to discuss the interpretation of the use of frozen language variety. The results of this study indicate that the use of frozen language varieties such as the words